Family reform and its link to solving the problems facing working women and their multiple roles: Applied study on a sample of women working in the private sector in Jeddah - Al-Mutairi, Samir Khalaf Atiq (Journal of Humanities & Social Sciences, 2023)
The study aimed to reveal the role of family reform and its linkage to the solution of problems faced by working women and their multiple roles. The study used the analytical descriptive curriculum. The study tool was a questionnaire form for data and information collection. The sample of the study consisted of 150 women working in the private sector in Jeddah. The findings of the study found that there is a high level of multiple roles assigned to working women of 2.543 and 0.654 deviations. There is an average level of problems faced by working women as a result of their multiple roles of 2.027 and 0.743 deviations. There is an average role of family reform in solving problems faced by working women of 2.287 and 0.720 deviations. and to raise awareness among individuals of the role played by family reform offices in resolving marital disputes and problems; Attention is given to urging companies and enterprises working in the private sector to identify working hours commensurate with women's abilities and potential.
Keywords: Family Reform; Working Women; Multiple Roles; Family Problems